The effectiveness of codetermination laws in cooperative and adversarial employment relations: When does regulation have bite?. (May 2015) - Backes-Gellner, Uschi; Mohrenweiser, Jens; Pull, Kerstin
The German Codetermination Law grants workers of establishments with 200 or more employees the right to have a works councillor who is fully exempted from his or her regular job duties while still paid a regular salary. This article analyses theoretically and empirically how this de jure right to exemption translates into de facto practice, and explicitly takes into account the nature of the employment relations participation regime. It is found that the right of exemption has no effect in cooperative employment relations because exemptions are granted even in the absence of legal rights, but does make a difference in adversarial relations when exemptions are only granted above the threshold where legal rights force employers to do so, i.e. legal rights do make a decisive difference in exactly those situations where the legislators' intent would not be realized without the right to legal enforcement.